Digging deep : the effect of design on the social behavior and attitudes of people working in underground workplaces in Europe - Venugopal, Vinita (2020)
With the cities of the world grappling with the ever-increasing challenge of land scarcity, sustainable solutions such as Underground Workplaces (UW) have been getting renewed interest. However, considering the hefty investments that will go into building UW and since the success of this solution relies on the wellbeing of the people who are to occupy it, there is a need to examine existing UW from a human factor point of view. In this paper, we present an analysis of how design factors in UW affect the attitudes and social behavior of employees and how these perceptions and attitudes towards the workplace vary across different work types. According to our analysis organic elements, art, architecture and lighting affect social behavior and attitudes. These factors can be manipulated according to the type of work and environment in a way that is in line with company values. The paper also attempts to create a framework for how the significance of the work environment varies with the type of work and workplaces.